Whey as crucial component in rejuvenating athlete health- a review - Anirudh, Jivanage; V, Dhineshkumar; T, Sangeetha (Journal of Postharvest Technology, 2022)
In this review, we have made an attempt to relate the essential component whey with athletes which is very crucial part of their  nutrition and its types and various outcomes of consuming this whey protein in the form of beverage which is ready to Drink juice as  intact as an substitute or alternative for the normal water for athletes during their regular bouts and Practice session. This Whey  beverage is having many benefits and it suits the condition of the athletes, mixture of a fruit juice in the combination of whey has  created a remarkably combo. Here we have also highlighted the whey importance components along with different combinations of whey fruit beverages which have got the best acceptability from the consumers. This content mainly focused on the whey beverage importance for the athletes as sports drinks, with essential commercialization benefit of whey It also has both biological and  common application of whey in various fields and how it can play an important part in the treatment of some serious illness. It plays  a role in the treating disease like Gastrointestinal infection can prevent in excess production of free radical, helps in treating  cardiovascular diseases, human immune virus (HIV), has good role in treating Hepatitis and Cancer. These are the common disease for the normal humans and also for the athletes this can be overcome easily with the help of whey based fruit beverage.
Keywords: Beverage; whey,; sports drink; cardiovascular disease; , dairy food